Acute Complications in Hemodialysis: Frequency, Patterns, and Clinical Implications: Acute Complications in Hemodialysis - Najumusaqib, Muhammad; Khan, Aimal; Sohail, Muhammad Waheed; Ullah, Zareen; Mehmood, Muzamil; Amin, Yousaf (Pakistan Journal of Health Sciences, 2025)
Chronic Kidney Disease (CKD) is a progressive and irreversible condition increasingly recognized as a global public health challenge. Hemodialysis, though life-sustaining, is frequently associated with acute complications that compromise patient outcomes and healthcare quality, especially in resource-limited settings. Objectives: To determine the frequency of acute complications during hemodialysis in patients with dialysis-dependent CKD at MTI Mardan Medical Complex, Mardan. Methods: This descriptive cross-sectional study was conducted from January to June 2025, involving 326 patients undergoing maintenance hemodialysis. Data were collected using a structured proforma documenting clinical and demographic characteristics, comorbidities, and intradialytic complications across multiple sessions. Standardized clinical definitions were applied to identify events such as hypotension (systolic BP drop ≥20 mmHg or <90 mmHg), hypoglycemia (RBS <70 mg/dL), and chest pain. The data were analyzed using SPSS version 20.0. Results: The mean age was 37.7 ± 12.1 years, with a male predominance (55.2%). The average duration of dialysis was 9.2 ± 5.1 months. Acute complications were observed in 41.7% of patients, with hypotension being the most frequently reported complication. Conclusions: Intra-dialytic complications are common in maintenance hemodialysis, with hypotension being the most prevalent. Enhanced monitoring, standardized protocols, and multicenter studies are warranted to reduce complication rates and improve patient care.